Quantum mechanical modeling of interstellar molecules on cosmic dusts: H2O, NH3, and CO2 - Fangfang Li; Fangfang Li; Donghui Quan; Donghui Quan; Xia Zhang; Xia Zhang; Xiaohu Li; Xiaohu Li; Jarken Esimbek; Jarken Esimbek (Frontiers in Chemistry, 2022)
Since the first detection of CH molecule in interstellar medium (ISM), more than 270 molecules have been identified in various astronomical sources in ISM. These molecules include big complex ones, such as fullerene (C60) and polycyclic aromatic hydrocarbons (PAHs), which are the main components of carbonaceous dust. Dust surface chemistry plays an important role in explaining the formation of interstellar molecules. However, many of the dust surface chemical parameters, such as the adsorption energies, are still of uncertainty. Here we present a study of the adsorption of water (H2O), ammonia (NH3), and carbon dioxide (CO2) on graphene-like substrate within the framework of density functional theory (DFT). We used Gaussian 16 software and adopted the corrected generalized gradient approximation (GGA) with the Perdew–Burke–Ernzerhof (PBE) functions. We determined the optimal accretion position of the studied molecules on the graphene-like surface and calculated the adsorption energies. Furthermore, according to the density of states and molecular orbitals of the adsorbed states, we analyzed the charge transfer between the molecules and the graphene-like surface. These results can provide more accurate parameters for calculating the chemical reaction rates on the dust surface, thus contributing to the understanding of dust-surface reactions in ISM.